Advances in Resist Materials and Processing Technology XXVI 2009
DOI: 10.1117/12.814342
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of EUV resists to out-of-band radiation

Abstract: Here we present the relative sensitivity of EUV resists to out of band radiation (OOB), specifically wavelengths in the range 157 -400 nm. EUV light sources have specifications limiting the allowed energy output in that spectral range yet there is little data supporting the specified values. Filters might be required to meet the spectral purity specifications which will likely have the detrimental effect of reducing the in-band radiation at 13.5 nm and therefore negatively impact the cost of ownership of EUV l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…These PAGs exhibited decreased Deep UV (DUV) absorption by the incorporation of insensitive cations and they were considered in resist formulations based both on blended PAG and polymer-bound PAG. The concept and merit of OoB insensitivity was confirmed by the obtained DUV and EUV sensitivity [49][50][51][52].…”
Section: Polymeric Systems Based On Hydrophilicity Changementioning
confidence: 57%
“…These PAGs exhibited decreased Deep UV (DUV) absorption by the incorporation of insensitive cations and they were considered in resist formulations based both on blended PAG and polymer-bound PAG. The concept and merit of OoB insensitivity was confirmed by the obtained DUV and EUV sensitivity [49][50][51][52].…”
Section: Polymeric Systems Based On Hydrophilicity Changementioning
confidence: 57%
“…Some of the EUV resists that are currently being utilized for patterning studies have been shown to be many times more sensitive to specific wavelengths in the 150-300nm DUV/UV region as compared to the sensitivity at 13.5nm [4]. This is of significant concern since the tin plasma based EUV light sources are known to produce quantifiable emission in this region along with the required source bandwidth.…”
Section: Introductionmentioning
confidence: 97%
“…9 Depending on the design the number of mirrors utilized for projection and imaging may vary and estimates for a 10 and 11 mirror system are given in table 1. Depending on the resist platforms utilized, the absorption of OOB wavelengths will vary 6 and this may lead to considerable reduction in patterning fidelity. Traditionally, flare from OOB is treated as a uniform background (DC) problem.…”
Section: Oob Related Flare Estimations At the Image Planementioning
confidence: 99%